Emotional intelligence of children with special needs using innovative technologies - Nurymov, Yermek; Nasyrova, Liliya (Institute of Advanced Engineering and Science, 2024)
The research examines the emotional intelligence of school-age children in Kazakhstan and Russia and develops a set of strategies to teach students emotional intelligence. The study was conducted on the basis of the Weisinger’s five-dimensional model methodological framework based on the classical model of Coleman’s emotional intelligence. The research bases on data collected from 185 secondary school teachers in Kazakhstan and Russia who work with children with special needs. The participants filled out an 11-item questionnaire with 10 closed and 1 open-ended question. The results revealed that emotional intelligence played a vital role in the overall development of children, especially those with special needs. The level of emotional intelligence was also diagnosed in 264 sixth graders in the study region using the Weisinger Emotional Intelligence test twice; second test after one month of informational technologies for emotional intelligence improvement use. The results of the first test indicate a low level of emotional intelligence in the studied sample of children with disabilities (female=55.4, male=37.5); the result of the second test showed statistically significant small changes for the better (from 44.19 to 48.92 mean score in the sample).